Edukasi Pemanfaatan Biji Nangka Berkhasiat sebagai Antibakteri - Suharyanisa Suharyanisa; Jon Kenedy Marpaung; Julia Susanti (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Jackfruit seeds contain several secondary metabolite compounds, including flavonoids, alkaloids, saponins, terpenoids and steroids. Jackfruit plants are one type of plant that can grow in tropical areas, so it is easy to find in Indonesia. The purpose of this community service is to improve and provide information and education to the community that the use of jackfruit seeds can be efficacious as an antibacterial. The results of the implementation of community service programs in the form of counseling to the community that there are benefits of jackfruit seeds used as antibacterial. So far, the public does not know that jackfruit seeds, which are often thrown away, can be efficacious as an antibacterial. The conclusion that the counseling was carried out according to the implementation and plan, received a good response from the surrounding community, the community also got information and knowledge and could apply the information for the family.